ANALISIS TINGKAT KERUSAKAN POHON DI RUANG TERBUKA HIJAU FAKULTAS PERTANIAN UNIVERSITAS LAMPUNG - Naila Putri Dwi Prana; Rahmat Safe'i; Machya Kartika Tsani (Jurnal Sylva Scienteae, 2024)
Faculty of Agriculture, University of Lampung is one of the GOS in urban. Currently, the conditions of tree damage at the GOS in Faculty of Agriculture are increasingly seen from old trees that are vulnerable to pest infestation. This amount of damage has a negative impact on the GOS to extent that it threatens safety of visitors inside. The purpose this research is to find conditions of damage trees at GOS of Faculty Agriculture, Lampung University. Data collection using the FHM method with  census technique to see the low height of damage trees at five locations that represent of Faculty Agriculture, University of Lampung. The result of this research is  the damage found at GOS of Faculty Agriculture mostly in the leaves, and least damage occurred in part of title rod. Types of damage include: cancer, resinosis/gumosis, open wounds, clay nests, broken stems, broke stems/roots, lianas, fractured/dead branches, disappearance of cracks/deads, leaves, damaged shoots, rust and leaves change colour. The highest tree damage index (TLI) is at Point 4 with value of 6,850 and the lowest TLI at Point 5 with value of 2,830. The average TLI value at GOS of Faculty of Agriculture is 4,514 (moderate category).